Comparing Behavioral Assumptions of Policy Tools: Framework for Policy Designers. Issue 6 (1st November 2020) - Olejniczak, Karol; Śliwowski, Paweł; Leeuw, Frans
Abstract: The article provides a comparative framework for articulating assumptions made during the policy design process. That includes the framing of the policy issue in terms of the behavior of addressees, identifying problems that obstruct compliance, and choosing a tool with a distinctive change mechanism. Based on this discussion, a spectrum of six generic policy tools have been provided and illustrated with examples: (1) equipping policy subjects to perform behavior, (2) banning misbehavior, (3) dis/incentivizing addressees to behave in a certain way, (4) informing to raise the awareness about need for compliance, (5) boosting, and (6) nudging towards desired behavior.